Morphology of the first zoeal stage of the partner shrimp Periclimenes amethysteus Risso, 1827 (Decapoda: Caridea: Palaemonidae: Pontoniinae) studied with the Scanning EM - Geiselbrecht, Hannes; Melzer, Roland R. (Zootaxa, 2009)
The morphology of the first stage zoea of Periclimenes amethysteus (Risso, 1827) is described and illustrated for the first time. Larvae were obtained from an ovigerous female, caught in Cross Bay, Rovinj, Croatia. The morphological characters are compared to previous larval descriptions of other known species of the genus Periclimenes (Costa, 1844) and a combination of three features is presented, which allows the first stage zoeae of P. amethysteus to be distinguished from the other already described species. The descriptions are based on dissected larvae analysed with SEM.